(MULTI)LETRAMENTOS NA COLEÇÃO CERCANÍA: UM OLHAR A PARTIR DO CONTEXTO DA AMAZÔNIA SUL-OCIDENTAL - Mendonça, Michelly Ferreira de (2022)
This research, whose theme involves the use of the textbook of Spanish as a Foreign Language (SFL) and the development of multiliteracies, defends the thesis that the principles of multiliteracies in the textbooks of SFL can enable the reflection of students from the Southern Amazon. Western in relation to the culture of Spanish-speaking countries, with which they border, and their own culture, as well as favoring contact with the multiplicity of languages of different discursive genres that circulate socially. The general objective is to verify if/how the textbooks of the Cercanía Collection are based on a multiliteracies approach, considering the border context of the SouthWestern Amazon. In order to do so, we had as guiding questions: i) How are the principles that support multiliteracies underlying the guidelines of the Cercanía Elementary School Collection? ii) In what aspects does the Cercanía collection make it possible to insert students from the final years of Elementary School in multiliteracies practices using SFL, in the border context of the South-Western Amazon, in which the city of Rio Branco/AC is inserted? Also, this study is inserted in the field of Applied Linguistics, having an exploratory interpretive qualitative nature, based on document analysis. The corpus consists of the Student's textbook and the Teacher's Manual of the 7th year of the Cercanía Collection, of Elementary School, referring to the PNLD 2017-2019. The theoretical framework is guided by different areas for the understanding of phenomena that involve the Dialogical/Interactionist Conception of Language, Literacy, New Literacies, Multiliteracies, Cultural Studies and Social Semiotics, based on authors such as García Canclini (1990 ; 1999; 2009; 2011), Hall (2003), Bakhtin (2011 [1979]), Fiorin (2011), Castela (2008), Cavalcanti and Maher (2009), Rojo (2012; 2013; 2017), Kress (2000) ; 2010), Cope and Kalantzis (2010; 2015); Candau (2012), among others. In order to achieve this, we divided the research into four stages: i) Survey of the Production Context of the ELE textbook; ii) Description of the Cercanía Collection; iii) Analysis of the Cercanía Collection Teacher's Manual; iv) Analysis of the Cercanía Collection Multiliteracies. The results show that the theoretical-methodological conception of the printed (and multimedia) Teacher's Manual is the socio-discursive approach of SFL. The collection's proposal is anchored in discourse genres and transversal themes. We found that the structure of the Collection comprises several sections that cover linguistic and cultural knowledge. These sections include the work with the four skills (reading, writing, speaking and listening), based on activities related to the different discursive genres that circulate in society, which in their compositional construction present several semiotic resources that aim to assist in the understanding of aspects textbook linguistic and cultural. These resources facilitate the understanding of the topics addressed, as the use of images, audio, together with writing, for example, allows expanding the production of meanings and senses in the utterances. Thus, although there is no specific proposal for multiliteracies, they present multiplicities of languages and cultures, with the use or not of Digital Information and Communication Technologies. Some situations present the context of the research, allowing the teacher to expand the more specific discussions about the local context. We hope that the results can help further research and reflection on the importance of multiliteracies practices, mainly related to teaching materials provided in schools, as in the case of textbooks. In addition, we hope that other studies will be carried out on the context and the highlighted theme.